(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
One of the leading directions in the development of secondary special vocational education institutions in the system of vocational education in modern socio-economic conditions is the multi-stage continuous professional training of highly qualified and competitive young professionals in integrated groups of professions. This is due to the development of science and technology, integration processes in the economy, science, technology and production, which have a qualitative impact on the nature and content of labor and labor functions.